Transboundary hazardous waste : its environmental effects and remedies. - HARPER, Glyne Leon (1993)
Discusses the various factors influencing hazardous waste disposal, including transboundary trading and dumping in non-industrialized countries. Highlights regulations which govern transboundary waste, viz. US Law, the Basel Convention, the Bamako Convention and the Rio Declaration.